2022
DOI: 10.1055/a-1747-9905
|View full text |Cite
|
Sign up to set email alerts
|

The Fate of Nonoperative Management in Patients with Lytic Spondylolisthesis

Abstract: Introduction: There is a lack of consensus within the current literature about the role of nonoperative management in lytic spondylolisthesis. Our objective was to assess the fate that nonoperative management plays in patients diagnosed with lytic spondylolisthesis. Material and Methods: Data was collected from 41 patients between May 2015 to February 2020 who were initially referred specifically for instrumented lumbar fixation but were instead planned for nonoperative management as they opted to avoid surger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The correlation of DS progression and intensity of pain is controversial [31]. Sinha and George [42] observed that even severe radiologic foraminal stenosis without radicular pain did not seem to push patients to undergo surgery. A recent meta-analysis depicted that not all patients with DS end up with significant pain/disability and eventually require surgery [31].…”
Section: Does Radiology Correlate With Clinical Findings?mentioning
confidence: 99%
“…The correlation of DS progression and intensity of pain is controversial [31]. Sinha and George [42] observed that even severe radiologic foraminal stenosis without radicular pain did not seem to push patients to undergo surgery. A recent meta-analysis depicted that not all patients with DS end up with significant pain/disability and eventually require surgery [31].…”
Section: Does Radiology Correlate With Clinical Findings?mentioning
confidence: 99%